Reflections of a Practitioner-Researcher in the Field of Widening Participation in Arts Education - Martell Baines; Margaret Gregson (MDPI AG, 2020)
This article provides an auto-ethnographic narrative to offer insights into my experience as a practitioner-researcher working in widening participation (WP) in post-compulsory education (PCE). It relates how I came to join the Education and Training Foundation (ETF) Practitioner Research Programme (PRP). It provides insights into the role of WP practitioner and manager and offers a reflection upon my experiences as an early practitioner-researcher conducting research in the field of WP. Writing in the first person, I reflect upon the positionality within my professional practice as someone who is immersed in the context that is being researched. I make my story as authentic as possible in order to throw new light upon knowledge in the field of widening participation (WP) practice. This immersion has enabled me to increase my professional knowledge and to establish a stronger voice in and for WP practitioners in the profession and for learners in the WP community. This empowerment has come about as my knowledge of the factors influencing the context of my work has expanded. I hope that it will be of interest to other researchers working in the field of WP and that they will accept my invitation to contribute to this conversation and reflect upon their own journey.